Fiscal policy design in low-income countries - Christopher S. Adam; David L. Bevan (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2001)
For many low-income countries, there has been an extended period in which fiscal policy was not a choice, or was a choice made by authorities external to the country. For a number of them, this situation is now changing. Their own success in stabilising the economy, coupled with a shift in the stance of the international community (most notably the IMF), has placed fiscal choices back on the domestic agenda. However, the scope for choice may be heavily circumscribed by the legacy of past fiscal laxity. There are two challenges to the domestic fiscal authority in these circumstances. First they must gauge how best to manage the transition from the immediate post-stabilisation period to the longer term (post-post-stabilisation). Second, they must see how these longer term fiscal choices can best accommodate the requirements of preserving macroeconomic stability with the encouragement of growth and poverty reduction.
Keywords: O23; O55; H62; 330; fiscal policy; macro-economic stabilization; sub-Saharan Africa; Finanzpolitik; Anpassungsprogramm des IWF; Entwicklungsländer